Transformasi Digital Keuangan Islam dalam Mendorong Inklusi Keuangan dan Penguatan Ekonomi Syariah - Nur Umamah; Andriani Samsuri (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Advances in digital technology have transformed the way people access, use, and manage financial services. In the context of the Islamic economy, financial digitization presents a significant opportunity to expand the reach of Sharia-compliant financial services, enhance financial literacy and inclusion, and strengthen the halal economic ecosystem. This article aims to analyze the development of digital Islamic finance as a current trend, particularly in digital Sharia banking services, Sharia fintech, the digitization of SME financial record-keeping, digital cash waqf, and financial product innovations based on Sharia maqashid. The method used is descriptive qualitative research with a literature review approach through the examination of various relevant scientific journals and books. The results of the discussion indicate that digital Islamic finance plays a crucial role in enhancing public access to Sharia financial services, particularly for the younger generation, SME operators, the agricultural sector, and communities not yet reached by formal financial services. However, the development of digital Islamic finance also faces challenges, such as low Sharia financial literacy, digital security risks, compliance with Sharia principles, and the need for adaptive regulations. Therefore, synergy between Sharia financial institutions, regulators, academics, industry players, and the public is essential to ensure that digital transformation proceeds in accordance with Islamic values and provides widespread benefits.